Educação profissional integrada ao ensino médio: uma análise da proposta no IFPR – campus Cascavel - Skrowonski, Daniela (2019)
This research investigates the professional education integrated to the Secondary School Level developed by the Federal Institutes of Education, Science and Technology, with its research’s field restricted to IFPR - Campus Cascavel - PR. The main purpose is to analyze the proposal of integrated professional education to the Secondary School Level of this Institute, verifying if it is directed towards a polytechnic/ technological formation. Therefore, the relationship between education and labor, the investigation of the historical process of public policies in professional education in Brazil, as well as the analysis of the professional education integrated to secondary school level promoted in IFPR - Campus Cascavel, are presented as an investigative path of the research, which is based on the dialectical historical materialism method, using authors such as Marx, Gramsci, Frigotto, Saviani, Ramos, Ciavatta, Ferretti, among others. For this reason, qualitative research is configured as evaluation, and the used methodology was bibliographical and documentary research, semi-structured interviews and a questionnaire, these last two being applied at Campus Cascavel. As the subjects involved in the interviews, stand out the campus employees, specifically the management, the pedagogical team and the teaching staff, investigating how the policy proposed by the Federal Institutes of integrated professional training is accepted and treated by them. In addition to these, students who were in training answered a questionnaire, in order to identify their perception of this formative process. Based on bibliographical studies, this research indicates the polytechnic education as a possibility of overcoming educational dualism, which allows an omnilateral formation, focused on the understanding of scientific foundations, integrating science, technology, culture and work. In addition, it emphasizes that the Federal Institutes are one of the most significant public policies with promising results to professional education integrated to secondary school levels, but, at the same time, they are institutions that promote capital. The research also points to threats related to professional education integrated to secondary school level, such as the against-reform of Secondary School Education and the offer of online courses and the Initial and Continuing Training (FIC) program offered by the Federal Institutes themselves. Finally, even in the face of certain challenges, such as the lack of continuous training, financial resources and physical infrastructure, we conclude that the professional education integrated to the Secondary School Level of IFPR – Campus Cascavel represents an initial path to polytechnic/ technological education, going beyond the demands of the market, committing itself to the full education of the individual.